Odpowiedź :
Odpowiedź:
1/ 6x= 42-12
6x = 30 // 6
x= 5
2/ -6x = 28 -40
- 6x = -12 // -6
x= 2
3/ 3x = 36 - 12
3x = 24 //3
x = 8
4/ 4x-7x = -24 +3
-3x = -21 // -3
x = 7
5/ 2a-a = 1+3
a= 4
6/ 4b-3b = -4-3
b = -7
7/ 3c-2c = 5 - 7
c = -2
8/ 5d - 3d = - 2
2d = - 2 //
d= -1
9/ 6y-9y = 5+7
-3y = 12// -3
y = -4
10/ 2x + 12 = -4
2x = -4 -12
2x = -16 // 2
x = -8
1. 6x = 42-12
6x = 30 \: 6
x= 5
3. 3x= 36 + 12
3x = 48 \:3
x= 16
4. 4x -7x= -24 + 3
-3x = -21\: (-3)
X= -7
5. 2a - a = 1+ 3
a= 4
( jak przed niewiadoma jest 1 to jej nie zapisujemy, jest w pamięci) wiec nie piszemy 1a, tylko a
6. 4b-3b = -4-3
b= -7
7. 3c + 2c = 5 -7
5c = -2
6x = 30 \: 6
x= 5
3. 3x= 36 + 12
3x = 48 \:3
x= 16
4. 4x -7x= -24 + 3
-3x = -21\: (-3)
X= -7
5. 2a - a = 1+ 3
a= 4
( jak przed niewiadoma jest 1 to jej nie zapisujemy, jest w pamięci) wiec nie piszemy 1a, tylko a
6. 4b-3b = -4-3
b= -7
7. 3c + 2c = 5 -7
5c = -2